Conformational Analysis of Milk Derived Tripeptides, IPP, VPP and LPP, and Investigation of Their Anti-COVID-19 Potentials by Molecular Docking and Molecular Dynamics Studies - Çelik, Sefa; AKYÜZ, SEVİM; Agaeva, Gulshen; E. Özel, Ayşen; Qocayev, Niftali M.; Agaeva, Ulker (Taylor & Francis Ltd., 2024)
Milk derived tripeptides IPP(Ile-Pro-Pro), VPP(Val-Pro-Pro) and LPP(Leu-Pro-Pro) have inhibitory effects on angiotensin converting enzyme, which plays a fundamental role in blood pressure systems. To discover the potentiality of the tripeptides as SARS-CoV-2 inhibitors, molecular docking analyses of IPP, VPP and LPP tripeptides with variety of SARS-CoV-2 enzymes, namely with Main protease, papain-like protease and Spike glycoprotein, were performed. Molecular dynamics simulations were performed to validate the stability of the IPP, LPP and VPP tripeptides docked into SARS-CoV-2 main protease within 50 ns time scale and ligand-receptor interactions were evaluated. Molecular docking and molecular dynamics studies showed that these food-derived tripeptides may be effective against COVID-19.
Keywords: Conformational Analysis; Molecular Docking; Molecular Dynamics; Tripeptides IPP; VPP And LPP